Penerapan Model Problem Based Learning (PBL) Berbantuan Alat Peraga untuk Meningkatkan Minat dan Hasil Belajar Fisika Siswa MA - Arik Pujiyanti; Ellianawati Ellianawati; Wahyu Hardyanto (Physics Education Research Journal, 2021)
The implementation of the 2013 curriculum led to several innovations in the learning process including using the Problem Based Learning (PBL) model. This study aims to determine the interests and learning outcomes of students after being treated with the PBL model assisted by teaching aids. This type of research is a pre-experimental study with a one-shot case study design. The research sample consisted of 14 students of MA Uswatun Hasanah Semarang. The data collection technique used a written test instrument and a student interest questionnaire. The results of this study indicate that the learning outcomes of students analyzed by the N-gain test have increased with an N-gain coefficient of 0.21 which is included in the low criteria. The percentage of students' interest in learning obtained an average result of 81.786% so that it is categorized as very good. The results also showed that the use of the PBL model resulted in 85% completeness of the learning outcomes of the Circular Motion material so it could be concluded that the PBL model assisted by teaching aids had an influence on the learning outcomes of students.